The low-carbon technology: expert view towards technology expectation to encourage Malaysia urban residents carbon-capability behaviour - Abas, Ani Shazwani; Mohd Yunos, Mohd Yazid; Mohd Isa, Nor Kalsum; Ismail, Nor Atiah; Abdul Aziz, Faziawati (Universiti Kuala Lumpur Publishing, 2016)
Malaysia, including in the Southeast Asia countries, is one of the most vulnerable regions to the global warming threats. Even though we are not the highest releases global carbon dioxide (CO2) countries, community action is essential to reduce the emissions significances. The carbon-capability behaviour, which promotes people’s ability and motivation to reduce daily emissions, somehow requires the technology interventions to facilitate such behaviours. This paper aims to present the expert view towards technology expectation among Malaysia urban residents in order to encourage their low-carbon capability behaviour. This study uses the qualitative approach by adopting the content analysis and the focus group discussions held among expert panels in relevant field. The analysis and discussion briefly discuss on the expert’s opinion and suggestion towards technological aspects that could assist Malaysia urban residents to at least perform the low-carbon capability behaviour. The issues concerning on the low-carbon technology related to urban residents is also highlighted in the summary.